2018
DOI: 10.1029/2018wr023566
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Distributed Conceptual Hydrological Model Building: A Generic Top‐Down Approach Starting From Lumped Models

Abstract: Changing environmental conditions might have severe impacts on future flood frequencies and water availability. In order to develop mitigation strategies by carrying out impact studies, lumped hydrological models might not suffice anymore and the need for flexibility in spatial resolution arises. Recent developments already allow to change the grid size of hydrological models depending on the needs and to use different spatial resolutions in parallel for different applications. These developments, however, sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 99 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…First, we did not pursue the highest spatial resolution. The graph neural network-based model GNRRM is developed at 4-km resolution in our case study, which is lower than other fully distributed rainfall-runoff modeling studies in 1km (Huang et al, 2019) or 250m (Tren andDe Niel, 2018) resolutions. However, the proposed method could be expanded to higher resolution theoretically with high-resolution rainfall data (Seo et al, 2019) and more computing resources or distributed computing (Agliamzanov et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…First, we did not pursue the highest spatial resolution. The graph neural network-based model GNRRM is developed at 4-km resolution in our case study, which is lower than other fully distributed rainfall-runoff modeling studies in 1km (Huang et al, 2019) or 250m (Tren andDe Niel, 2018) resolutions. However, the proposed method could be expanded to higher resolution theoretically with high-resolution rainfall data (Seo et al, 2019) and more computing resources or distributed computing (Agliamzanov et al, 2020).…”
Section: Discussionmentioning
confidence: 80%
“…Same conclusion holds for the baseflow conditions at the internal stations, where all three coupled models improve the baseflow hydrographs compared to the simulation results of the distributed rainfall‐runoff model (Table ). Except for Meerhout station, where the measurement quality is limited (Tran et al ., ). Better performance at local gauging stations indicates the enhancement of the models over the distributed rainfall‐runoff model at simulating the spatially distributed groundwater discharge condition.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, Lobligeois et al (2014) showed that for basin exhibiting highly variable precipitation fields, the use of a distributed over a lumped model improved streamflow simulations. The benefits of distributed models is nevertheless wider than their ability to achieve better streamflow simulations (Tran et al, 2018). They provide spatially distributed information of key hydrological variables and processes.…”
Section: Discussionmentioning
confidence: 99%